Renal outcomes in pediatric patients with sickle cell disease: a single center experience in Saudi Arabia - Monagel, Dania A.; Algahtani, Shatha S.; Karawagh, Lian A.; Althubaity, Wafa D.; Azab, Sara A.; Haneef, Deena F.; Elimam, Naglla (Frontiers in Pediatrics, 2023)
Sickle cell nephropathy (SCN) is a significant complication of sickle cell disease (SCD) with an asymptomatic onset in childhood and potential progression to chronic kidney disease (CKD).The clinical findings of SCN include hyposthenuria, hematuria, proteinuria, hyperfiltration, and CKD. Data on renal manifestation among patients with SCD in Saudi Arabia is lacking.Therefore, this study aimed to evaluate renal outcomes in patients with SCD who visited a hematology clinic at the National Guard Hospital, Jeddah.We conducted a retrospective chart review of renal complications in patients with SCD who are within 0-14 years of age and on regular follow-ups at the pediatric hematology clinic in King Abdulaziz Medical City-Jeddah, Saudi Arabia.Among the 140 patients with SCD, 99 met the inclusion criteria. The median age at diagnosis was 18 (1-108) months. Two SCD phenotypes were observed, with 82 (83%) patients having sickle cell anemia (HbSS) and 17 (17%) having HbS/B + thalassemia. Of the total patients, 92 (93%) were administered hydroxyurea (HU), with a median starting age of 48 (9-168) months.The most common renal complication observed during routine urinalysis was hematuria (38%), followed by proteinuria (11%). After stratifying the sample into four age groups (0-3 years old, 4-7 years old, 8-11 years old, and 12-14 years old), the mean glomerular filtration rate (GFR) values were 96.16, 101.36, 112.69, and 120.11 mL/min/1.73 m 2 respectively. Renal imaging revealed abnormal findings in 27 (29%) patients. The most common abnormality observed on US was increased echogenicity (43%).SCN is a significant complication of SCD. In this study, we assessed the renal outcomes in pediatric patients with SCD. After analyzing the clinical findings of SCN, we concluded that the presence of renal complications in pediatric patients presented a progressive pattern.